Consumerism and the “fall of Babylon” - Pereyra Lavandina, Mario (2011)
From the 18th century one installs the modernism that there promoted the objective evi- dence, the rational usefulness and the discovery of the laws of the nature. From the second part of the 20th century, there sinks the ingenuous optimism of the indefinite progress and there is born a new type of individualistic company, centre on the present, which favors the consumption and the hedonism: the postmodern era. The consumer fever of immediate satisfactions to continued during the 21st century in what it is being called the hypermo- dernity, wilder than never, though wrapped in a halo of dreads and uneasiness’s. There is investigated the historical process that gave place to the hyperconsumption later to raise if perhaps this one is the last stage of the history or if there will be a poshypermodernism. The sociologist Z.Bauman (2007) thinks that the possibility of producing a new type of culture is practically void. From this irreversible reality is considered to be the apocalyptic prophecy of Babylonia (Rev.18), in his catastrophic conclusion, a final event of the human history, think- ing that it relates to the economy and the politics, as sociocultural key axes, doing the Biblical text a description that might relate to organizations that work from the shades handled by the most powerful clans of the world, which would be directing the flows of the big capitals and influencing the international politics moved by the avidity of power, in perverse and selfish form. It might hypothetizar that the apocalyptic prophecy of the last Babylonian sym- bolism might apply to him to the hypermodernism, there being augured his destruction and the installation of a new order under the patronages of the Divine Being.Keywords: Modernism, culture, consumerism, society.